Factors to be taken into account when choosing a method of peaceful settlement of international disputes. (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The obligation to search for peaceful solutions to settle international disputes has become a general obligation and imposed on all states, and this commitment is linked to another principle, which is the prohibition of the use of force or the threat to use it in international relations.The means of peaceful settlement are varied, giving the states parties to the conflict the freedom to choose the method they deem appropriate to settle it in a just manner. And the decision that the government takes to choose the means of settlement is a political decision because it was issued by a political body and has great importance as it relates to the management of international relations. And decision-making is not done selectively, but rather according to objective factors and after weighing the different means.Studying objective factors and identifying the characteristics, advantages and disadvantages of a method according to each conflict helps those charged with expressing the state’s will to make a rational decision when choosing a settlement method. Also, being familiar with the state’s practices in this regard enhances confidence in the decision. Given the sensitivity of the subject, I will highlight in this research on The most important factors and considerations that must be taken into account when choosing a means of peaceful settlement of international disputes.